2011
DOI: 10.1007/s10856-011-4530-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of human primary bone cells with biphasic calcium phosphate (βTCP/HA 70:30) granules increases bone repair

Abstract: This work evaluates the suitability of biphasic calcium phosphate (BCP) granules (β-TCP/HA 70:30) as potential carriers for cell-guided bone therapy. The BCP granules were obtained by synthesis in the presence of wax, thermal treatment, crushing and sieving and characterized by scanning electron microscopy (SEM), X-ray diffraction and Fourier transform infrared spectroscopy. The cytocompatibility of the BCP granules was confirmed by a multiparametric cytotoxicity assay. SEM analysis showed human bone cell adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
1
15
0
5
Order By: Relevance
“…The data from this study demonstrated that, clinically, all biomaterials used were adequate for alveolar filling after tooth extraction, in addition to being biocompatible and osteoconductive. This osteoconduction is favored due to the porous environment that is presented by the sphere and granule formats of the used biomaterials [27,28]. The CHA group was developed in spherical form because of the previously confirmed reduction on inflammatory response when compared to the needle shape [24].…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study demonstrated that, clinically, all biomaterials used were adequate for alveolar filling after tooth extraction, in addition to being biocompatible and osteoconductive. This osteoconduction is favored due to the porous environment that is presented by the sphere and granule formats of the used biomaterials [27,28]. The CHA group was developed in spherical form because of the previously confirmed reduction on inflammatory response when compared to the needle shape [24].…”
Section: Discussionmentioning
confidence: 99%
“…The use of spheres or granules to biocompatible materials for clinical use has been previously proposed 6 , 21 , 24 , as they may be injectable and moldable, and simulate a porous environment for increased osteoconductivity. In this context, carbonated nanostructured hydroxyapatite/sodium alginate spheres may be a promising biomaterial for bone replacement.…”
Section: Discussionmentioning
confidence: 99%
“…A menor quantidade de pesquisas in vitro reflete a necessidade de maior busca por métodos alternativos ao uso de animais para testes de biomateriais, por outro lado, sem desconsiderar suas limitações técnicas e de eficácia (Cosme et al, 2017). De fato, as pesquisas normalizadas pré-clínicas por novos produtos odontológicos são fundamentais para progressão aos testes em humanos (Luz et al, 2020;Bittencourt et al, 2014;Lomelino et al, 2011).…”
Section: Discussionunclassified
“…A regeneração óssea guiada (ROG) em Odontologia é tema de pesquisas multidisciplinares e translacionais, por envolver desde o desenvolvimento laboratorial de biomateriais até as caracterizações biológicas normalizadas de validação para uso clínico (Bittencourt et al, 2014;Lomelino et al, 2011). Os biomateriais para ROG podem ser diferenciados quanto a aplicação (em especial, membranas para barreira e enxertos ósseos), origem (autógena, alógena, xenógena ou aloplástica) e composição (biocerâmicas e biovidros, polímeros ou compósitos), estando presentes na prática clínica e exibindo boa aceitação geral da classe odontológica (Araújo et al, 2020;Castro-Silva & Coutinho, 2012).…”
Section: Introductionunclassified